Protestants and Catholics and educational investment in Guatemala - Robert J. Barro; Rachel M. McCleary (American Enterprise Institute (AEI), 2017)
Barro and McCleary look at differential investment in education across types of Protestantism. They find that literacy is enhanced more by Mainline Protestant schools then by Other Protestant schools and that Catholic schools have the weakest relation with literacy, likely because the ouster of Catholic orders and schools in the liberal reforms of the 1870s had a lasting influence.
Keywords: A; 330; catholicism; protestant